TESTING ON REAL USE AND USER SATISFACTION ENTERPRISE RESOURCE PLANNING ON BANKING COMPANIES IN WEST SUMATERA - Dandes Rifa Dandes Rifa; Siti Rahmi Siti Rahmi; Daniati Puttri Daniati Puttri (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2018)
Enterprise Resource Planning (ERP) is a way to manage company resources using information technology. The use of ERP is intended to coordinate and integrate data and information on each business unit (area business process) in order to produce more quality decision making because ERP provides financial reports and analysismore quickly, accurately and on time (on time). This study aims to test level of real use and ERP user satisfaction in existing banking companies in the West Sumatra region. The analysis was carried out by examining the effect of system quality, information quality and service quality on the level of real use and ERP user satisfaction in banking companies in West Sumatra. Data acquisition is done by survey techniques through questionnaires to 140 employees of 4 government banks in WestSumatra (ERP users). A total of 89 data can be processed in this study. Multiple regression analysis statistical tests are used to test hypotheses.Regression test results on model I indicate that there is no influence ofinformation system quality, information quality and service quality on the level of real use of Enterprise Resource Planning. Meanwhile the test results on model II show that there is an influence of information system quality, information quality and service quality on the satisfaction of Enterprise Resource Planning users.